2016
DOI: 10.1371/journal.pntd.0005109
|View full text |Cite
|
Sign up to set email alerts
|

Human IgG Antibody Response to Aedes Nterm-34kDa Salivary Peptide, an Epidemiological Tool to Assess Vector Control in Chikungunya and Dengue Transmission Area

Abstract: BackgroundArboviral diseases are an important public health concerns. Vector control remains the sole strategy to fight against these diseases. Because of the important limits of methods currently used to assess human exposure to Aedes mosquito bites, much effort is being devoted to develop new indicators. Recent studies have reported that human antibody (Ab) responses to Aedes aegypti Nterm-34kDa salivary peptide represent a promising biomarker tool to evaluate the human-Aedes contact. The present study aims … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 44 publications
1
45
0
Order By: Relevance
“…aegypti and that of Ae. albopictus [ 29 ], the second principal vector of arboviruses worldwide. Indeed, IgG Ab response against the Nterm-34 kDa peptide identified in Ae.…”
Section: Potential Applications Of Aedes Salivamentioning
confidence: 99%
See 3 more Smart Citations
“…aegypti and that of Ae. albopictus [ 29 ], the second principal vector of arboviruses worldwide. Indeed, IgG Ab response against the Nterm-34 kDa peptide identified in Ae.…”
Section: Potential Applications Of Aedes Salivamentioning
confidence: 99%
“…A recent study has reported that human IgG response to the Ae. aegypti Nterm-34 kDa peptide could be used for assessing the effectiveness of VCS against Aedes [ 29 ]. During this study, specific IgG response was assessed from 102 individuals living in urban area in La Reunion Island before and after the implementation of VCS against Ae.…”
Section: Potential Applications Of Aedes Salivamentioning
confidence: 99%
See 2 more Smart Citations
“…To improve the surveillance and control of mosquito-borne diseases, people exposed to mosquito bites were assessed to develop immunological indicators of specific human antibody responses against salivary peptides from Aedes (Nterm-34-kDa) and Anopheles (gSG6-P1). These antibody-based biomarkers were validated by several studies as relevant tools to accurately evaluate (1) the risk of malaria [19][20][21][22][23][24] and arboviruses transmission [25,26] in several settings, including urban areas, and (2) the effectiveness of different vector control strategies [27][28][29][30]. The aim of the present study was to evaluate the spatial heterogeneity of exposure to both vectors of malaria and arboviral diseases in a northern urban area of Senegal, using antibody-based biomarkers of human exposure to Anopheles and Aedes mosquito bites.…”
mentioning
confidence: 99%